2018
DOI: 10.1111/jdv.15147
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibody profile and clinical patterns in 619 Italian patients with cutaneous lupus erythematosus

Abstract: According to our findings, some well-known associations between CLE subtypes and autoantibody profile were confirmed; moreover, specific association between autoantibodies and LE-non-specific skin lesions was highlighted. A strict association between anti-ENA and anti-Ro/SSA antibodies and livedo reticularis, ANA and palpable purpura, and ANA and periungual telangiectasia was evidenced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 42 publications
1
17
0
4
Order By: Relevance
“…In the group of 65 LET patients, 60% were female, showing less gynecotropy in comparison with other CLE or SLE patients 27. In a cohort of 100 LET patients referred to a specialized tertiary dermatology centre in Germany, we reported similar gender findings (females 68%), as did a recent multicentre study of CLE in Italy, in which 72/108 LET patients (66.7%) were females 28,29…”
Section: Epidemiologysupporting
confidence: 80%
See 1 more Smart Citation
“…In the group of 65 LET patients, 60% were female, showing less gynecotropy in comparison with other CLE or SLE patients 27. In a cohort of 100 LET patients referred to a specialized tertiary dermatology centre in Germany, we reported similar gender findings (females 68%), as did a recent multicentre study of CLE in Italy, in which 72/108 LET patients (66.7%) were females 28,29…”
Section: Epidemiologysupporting
confidence: 80%
“…Verdelli et al included 108 LET patients in their recent, multicentre Italian study of 619 patients with CLE. 47 of them (43.5%) were ANA positive (titration not mentioned), while 24 (22.2%) were tested positive for anti-Ro/SSA-, 5 (4.6%) for anti-La/SSB-, 4 (3.7%) for anti-Sm- and 4 (3.7%) for anti-ds-DNA antibodies 29. These are the highest scores of positive ANA tests ever reported in patients with LET.…”
Section: Antinuclear Antibodies (Ana)mentioning
confidence: 98%
“…Systemic lupus erythematosus is a chronic immunemediated connective tissue disease affecting multiple organ systems and characterized by the generation of autoantibodies, deposition of immune complexes and activation of the complement system [25]. The antibodies most commonly associated with SLE include antinuclear antibodies, anti-double-stranded DNA and anti-Sj€ ogren's-syndrome-related antigen A antibodies [26]. SLE is one of the most heterogeneous illnesses with unpredictable clinical presentation, course and outcome.…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%
“…A recent study in a cohort of Italian CLE patients found strong correlations between autoantibody specificities and CLE subtypes ( 40 ). CCLE is negatively associated with anti-extractable nuclear antigens (ENA), anti-Ro/SSA, and anti-dsDNA.…”
Section: Autoantibodies/autoantigensmentioning
confidence: 99%